Controllable fabrication and catalytic activity of highly b‐oriented HZSM‐5 coatings. Issue 6 (20th April 2014) - Ji, Meiling; Liu, Guozhu; Wang, Li; Zhang, Xiangwen
Significance Multilayer b‐orientated HZSM‐5 catalytic coating is controllably synthesized by repeated growth of zeolite layer on TiOH‐modified surface of sublayer. The as‐prepared zeolite coating shows performance enhancement up to 110% in catalytic cracking of n‐dodecane ascribed to enhanced mass transfer in its straight and short pathway along the b‐axis. © 2014 American Institute of Chemical Engineers AIChE J, 60: 1964–1968, 2014